Non-English speaking witnesses in the Australian legal context : the War Crimes Prosecution as a case study - L. Stern (Law Text Culture, 1995)
This paper has its origin in a request from the Director of Public Prosecutions of South Australia to provide a linguistic report to be tendered in court during the 1992 committal hearing of Heinrich Vaguer, a defendant in one of the Australian War Crimes cases. The need for such a report emerged shortly after the commencement of the committal heanng of Ivan Polyukhovich, the first man charged with War Crimes in Australia, at which witnesses from Russia and Ukraine began to give their evidence in April 1992. It was felt by the court that there were serious communication problems between the legal profession on the one hand, and the Soviet witnesses on the other, and the author was asked to identify these problems and explain the reason for their occurrence. Although not a sociolinguist, the author was approached as someone who had an understanding of the languages used by the witnesses and of their socio-cultural background, as well as experience in the area of interpreting and translating. It was hoped that the report would help to prevent some of the communication problems in subsequent cases involving Soviet witnesses.